Cost-Effectiveness of Insulin Glargine and Insulin Detemir in the Basal Regimen for Naïve Insulin Patients with Type 2 Diabetes Mellitus (T2DM) in Malaysia - Shafie AA; Ng CH (Dove Medical Press, 2020)
Asrul Akmal Shafie,1 Chin Hui Ng2 1Discipline of Social and Administrative Pharmacy, School of Pharmaceutical Sciences, Penang, Malaysia; 2Pharmacy Department, Hospital Raja Permaisuri Bainun, Ipoh 30450, Perak, MalaysiaCorrespondence: Asrul Akmal ShafieDiscipline of Social and Administrative Pharmacy, School of Pharmaceutical Sciences, 11800 Universiti Sains Malaysia, Penang, MalaysiaEmail aakmal@usm.myObjective: To compare the cost-effectiveness of long-acting insulin analogue (LAIA) (insulin Detemir and insulin Glargine) versus NPH insulin in the basal insulin regime for naïve insulin T2DM Malaysian patients.Methods: The UKPDS-Outcome Model version 2.0 (UKPDS-OM2) was used to evaluate the cost and consequence of diabetes-related complication. The effectiveness of the insulin was derived from the literature review, and the patients’ epidemiology characteristics were retrieved from the Malaysian Diabetes Registry. A discount rate of 3% was applied to both costs and health effects. Another simple mathematical model was used to compare the benefit of reducing the hypoglycemia events between LAIA and NPH insulin. The outputs of the models were combined to obtain the final result. One-way sensitivity analyses were performed to assess the uncertainties.Results: The net cost difference (without accounting for hypoglycemia) was RM4868 for insulin Glargine and RM6026 for insulin Detemir. The saving from preventing severe hypoglycemia was RM4377 for insulin Glargine and RM12,753 for insulin Detemir. The total additional QALY gained from insulin Glargine was 0.1317 and from insulin Detemir was 0.8376. The sensitivity analysis shows the discount rate, and drug acquisition cost may affect the incremental cost-effectiveness ratio (ICER) value.Conclusion: Both insulin Detemir and Glargine are cost-effective compared to NPH insulin for T2DM patients, especially when the benefit of reducing the hypoglycemia event rate is taken into account.Keywords: type 2 diabetes mellitus, insulin Glargine, insulin Detemir, cost-effectiveness analysis